2006
DOI: 10.22329/jtl.v4i1.84
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Accommodation in Higher Education: A Survey of Adaptive Technology Use in Ontario Universities

Abstract: This paper provides an overview of adaptive technologies currently being used in Ontario Universities. Results of this study may help disability service providers in Ontario in understanding the current challenges of training students with disabilities in using adaptive technologies as well as improving service delivery methods. Participants were recruited through a listserv and asked to answer an online survey. Data were analyzed using descriptive statistics and anecdotal narratives. Results indicated that st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Other survey studies like Gaiters-Fields (2005), Abreu-Ellis & Ellis (2006), Klemes et al (2006) reported only descriptive statistics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other survey studies like Gaiters-Fields (2005), Abreu-Ellis & Ellis (2006), Klemes et al (2006) reported only descriptive statistics.…”
Section: Resultsmentioning
confidence: 99%
“…All students ( n = 10) used AT, but self-funded their AT due to little support from the university. Abreu-Ellis & Ellis (2006) surveyed professionals who worked in disability services offices in 17 universities of Ontario, Canada. Most participants strongly agreed that incoming students with LD needed to be trained in using AT and indicated that their university provided this service on a one-on-one basis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distributive model tends to facilitate integration of students with LD into the mainstream student body and is consistent with the principles of universal instructional design, a dominant pedagogical format in postsecondary environments, which calls for multiple means of representation, action and expression, and engagement. However, the need for increased funding to effectively deliver this model and a lack of institutional resources (e.g., specific AT knowledge at different locations, space, staffing, and hardware requirements) have been found to be major impediments to the implementation of this model (Abreu-Ellis & Ellis, 2006). The central location model has been found to result in greater levels of student satisfaction and success as well as more efficient delivery of services when compared to a distributive model (Burgstahler, 1992).…”
Section: Overview Of Delivery Of At Services At Postsecondary Institumentioning
confidence: 99%
“…However, it has been criticized for creating stigma in association with the use of AT through its sole and thus obvious point of distribution. Perhaps this is why the majority of postsecondary disability service providers in the United States (Burgstahler, 1992) and Ontario (Abreu-Ellis & Ellis, 2006) endorse the distributive location model of AT.…”
Section: Overview Of Delivery Of At Services At Postsecondary Institumentioning
confidence: 99%